Development of Amorphous Oxide Thin Film Transistors Fabricated by a Total Solution Process for Display Application. Issue 1 (June 2014) - Tue, Phan Trong; Koyama, Hiroaki; Li, Jinwang; Inoue, Satoshi; Shimoda, Tatsuya
Abstract First, we introduce a new oxide channel material, zirconium‐indium‐zinc‐oxide (ZIZO), with high performance and high stability. Second, we develop a totally solution‐derived process for fabricating active‐matrix TFTs for display application. The obtained TFT performance is better than a‐Si TFT and comparable to that of vacuum‐processed oxide TFTs.